2020
DOI: 10.2118/197804-pa
|View full text |Cite
|
Sign up to set email alerts
|

Deformable Microgel for Enhanced Oil Recovery in High-Temperature and Ultrahigh-Salinity Reservoirs: How to Design the Particle Size of Microgel to Achieve Its Optimal Match with Pore Throat of Porous Media

Abstract: Summary Conformance control treatment in high-temperature and ultrahigh-salinity reservoirs for easing water/gas channeling through high-permeability zones has been a great challenge. In this work, we propose a deformable microgel that can be used at more than 373.15 K and ultrahigh-salinity conditions (total dissolved solids  > 200 kg/m3, Ca2+ + Mg2+ > 10 kg/m3) and present a method for choosing the suitable particle size of the microgel to achieve an optimal match with the pore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…After the injection of 0.5 PV AMPS/AM microgel particles, the resistance factor was 58.05 and 41.04 under the permeability of 509.3 and 3011.2 mD, respectively, and final plugging ratios were 98.28 and 97.56%, respectively. The resistance factor decreases with permeability, which indicated that the resistance of the AMPS/AM microgel particles will decrease in the large pore with high permeability, but it still has a good plugging performance due to the larger seepage resistance caused by the full expansion of the AMPS/AM microgel particles in the small pore with low permeability. , When the permeability was 1039.4 and 3040.6 mD, the plugging ratios were 98.25 and 93.85%, respectively, after the injection of the 0.5 PV AMPS/AM microgel particles with a mass fraction of 0.2 wt %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the injection of 0.5 PV AMPS/AM microgel particles, the resistance factor was 58.05 and 41.04 under the permeability of 509.3 and 3011.2 mD, respectively, and final plugging ratios were 98.28 and 97.56%, respectively. The resistance factor decreases with permeability, which indicated that the resistance of the AMPS/AM microgel particles will decrease in the large pore with high permeability, but it still has a good plugging performance due to the larger seepage resistance caused by the full expansion of the AMPS/AM microgel particles in the small pore with low permeability. , When the permeability was 1039.4 and 3040.6 mD, the plugging ratios were 98.25 and 93.85%, respectively, after the injection of the 0.5 PV AMPS/AM microgel particles with a mass fraction of 0.2 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…Microgel is one of the profile control agents that can achieve remarkable profile control and EOR performance. The granuliform gel particles can enter the deep part of reservoirs and form a gel swelling body. In the high permeable area, the large gel expansion body could block the big pore, divert the water flow to the low permeable region, and extend the swept efficiency of water flooding. The successful application of gel particles has significantly improved the development efficiency of high water-cut reservoirs. However, there are still some problems faced by profile control treatments using microgel particles. For example, with the migration of microgel, the particles will gradually break up under the extrusion deformation and shear action of heterogeneous porous media, reducing the ability of gel particles to plug the big pore throat. Therefore, how to improve the mechanical strength of microgel particles and enhance their crushing resistance, achieving both an effective plugging and a deep remigration, has become a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the article [ 59 ] studied the matching factor of PPG in coreflooding experiments. Matching factor is the ratio of the PPG’s average diameter to the average pore-throat diameter.…”
Section: Methodsmentioning
confidence: 99%
“…After 90 days of exposure under such conditions, the particles did not show signs of degradation maintaining good dispersibility. Core flooding experiments showed a strong plugging effect with 93.13 % of residual resistance for rock cores with 54-100 D permeability [30,72]. AM-based polymeric microgels displayed good stability when exposed to brines of 215 000 ppm (200 000 ppm NaCl + 15 000 ppm CaCl 2 ).…”
Section: Microgelsmentioning
confidence: 99%